2021
DOI: 10.1111/febs.16275
|View full text |Cite
|
Sign up to set email alerts
|

eIF4E‐homologous protein (4EHP): a multifarious cap‐binding protein

Abstract: The cap-binding protein 4EHP/eIF4E2 has been a recent object of interest in the field of post-transcriptional gene regulation and translational control. From ribosome-associated quality control, to RNA decay and microRNA-mediated gene silencing, this member of the eIF4E protein family regulates gene expression through numerous pathways. Low in abundance but ubiquitously expressed, 4EHP interacts with different binding partners to form multiple protein complexes that regulate translation in a variety of biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 163 publications
0
17
0
1
Order By: Relevance
“…8a). To investigate the helical organization of GIGYF2 (744-940), we mapped this region back to a full-length threedimensional model of human GIGYF2 as predicted by AlphaFold 2 16,41 . GIGYF2 (744-940) corresponds to a region in the model that is confidently predicted (Extended Data Fig.…”
Section: Functional and Structural Characterization Of The Interactio...mentioning
confidence: 99%
See 1 more Smart Citation
“…8a). To investigate the helical organization of GIGYF2 (744-940), we mapped this region back to a full-length threedimensional model of human GIGYF2 as predicted by AlphaFold 2 16,41 . GIGYF2 (744-940) corresponds to a region in the model that is confidently predicted (Extended Data Fig.…”
Section: Functional and Structural Characterization Of The Interactio...mentioning
confidence: 99%
“…Consequently, 4EHP represses mRNAs translation upon recruitment to target mRNAs (e.g. via 4E-T protein upon recruitment by microRNAs) [16][17][18][19] . GIGYF2 [Grb10-interacting GYF (glycine, tyrosine, phenylalanine) protein 2] is another protein among others that is recruited by 4EHP to the mRNA to inhibit translation or decrease stability [20][21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…The role of 4EHP-GIGYF2 as a translational repressor has been described in various contexts (for review, see (Christie and Igreja, 2021)). Having shown that NSP2 directly targets the 4EHP-GIGYF2 complex through at least two contact points, namely the region 743-1,085 of GIGYF2 and 4EHP itself, we wished to assess whether the silencing capacity of 4EHP-GIGYF2 could be altered by NSP2.…”
Section: Nsp2 Reduces the Silencing Capacity Of Gigyf2mentioning
confidence: 99%
“…The cap-binding eIF4E-Homologous Protein (4EHP) is an integral component of post-transcriptional silencing mechanisms through competing with the eIF4F complex for binding to the mRNA 5 0 cap (Christie and Igreja, 2021). In complex with the GRB10-interacting GYF (glycine-tyrosine-phenylalanine domain) protein 2 (GIGYF2), the cap-binding activity of 4EHP is required for the optimal translational repression by mi-croRNAs (miRNAs), as well as the RNA-binding proteins ZNF598 and tristetraprolin (TTP) (Morita et al, 2012;Fu et al, 2016;Villaescusa et al, 2009;Cho et al, 2005Cho et al, , 2006Chapat et al, 2017b;Chen and Gao, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Drosophila eiF4E1-related protein eiF4EHP and its mammalian homolog eiF4E2 were primarily described as translational repressors of several mRNAs. However, eiF4E2 has also been reported to specifically activate mRNA translation in different cellular contexts including hypoxia (reviewed in 21 ). Interestingly, hypoxic treatment induces an increase of eIF4EHP detected in both head (Fig.…”
Section: Eif4ehp Promotes the 3'utr-dependent Translation Of Ldh Mrna...mentioning
confidence: 99%